P240 Smartinhalers – A New Approach To Assessing Adherence In Difficult Asthma. (10th November 2014) - Hall, P; Bracken, M; Winch, D; Nagakumar, P; Bush, A; Saglani, S; Fleming, L
Abstract : Introduction: Poor adherence is one of the key determinants of sub-optimal asthma control in children. Correctly identifying children with poor adherence can avoid unnecessary escalation of treatment and enable a targeted adherence intervention. Objective: To use electronic monitoring devices (Smartinhalers) to measure adherence to inhaled corticosteroids (ICS) in children with problematic severe asthma (PSA) and compare the data with prescription uptake and symptoms during the monitoring period. Methods: Smartinhalers were issued to patients for a 6–8 week study period as part of an established nurse led assessment in a tertiary referral centre. Advice regarding adherence and the purpose of the Smartinhalers was explained to all children and their parents. Lung function, bronchodilator reversibility, exhaled nitric oxide (FENO), mini paediatric asthma quality of life questionnaire (mPAQLQ), and asthma control test (ACT) were recorded at baseline and follow up. Wilcoxon signed ranks was used to compare visit 1 and visit 2 data. GP prescription uptake for ICS and number of salbutamol canisters issued in past year were obtained. Results: 33 children (21 male), median age 13 (5–17) years) were issued with Smartinhalers. 15 had adherence >80%, 14 between 50–80% and 4 < 50%. ACT and mPAQLQ improved significantly over the monitoring period (Figures 1 and 2). Children with a prescription uptake of <80% had a significant improvement in ACT compared to those with pick up of ≥80% (median change 3.5 (IQR 0.75–7.25) vs 0 (-4–3)) and a non-significant trend towards improvements in FEV1 and BDR. There was no relationship between prescription uptake and Smartinhaler adherence or salbutamol inhalers collected. Conclusion: Even when children know they are being monitored over half used <80% of the prescribed dose. Improvements in objective markers of asthma control during the monitoring period can help to identify those who were previously poorly adherent. Smartinhalers are useful tools in the assessment of adherence in conjunction with GP prescriptions and clinical observations.